The image of Alexander Kerensky in the memoirs of the White movement leaders of Southern Russia - Hlibischuk, M. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract Historians have written much about the Russian Revolution (1917–1922). However, there are topics that have been insufficiently studied. One of them is the image of state power and its perception during the revolution. The author analyzes how the White movement leaders of Southern Russia in 1917 perceived Alexander Kerensky, the leader of the Russian Revolution. Therefore, based on the memoirs of the author, we tried to analyze this issue. The author argues that the idea, prevalent in the Soviet historical science, that all the leaders of the White movement had a negative attitude towards Kerensky is incorrect. Military generals, who supported the White movement, actively criticized him for actions that were destructive for the Russian army. Many criticized him for that even when he already lived in exile. However, Generals Denikin and Alekseyev hoped that despite everything he would have been able to save the country from anarchy and prevent the Civil War. Politicians, who supported the White movement, also believed that Kerensky could prevent the collapse of the army and the state. For example, V. Shulgin believed that Kerensky would become a "Russian Napoleon", who would put an end to the revolution and not allow the Bolsheviks to take the power. However, after the conflict between General Kornilov and Kerensky, which occurred in August 1917, the leaders of the White movement became disillusioned with him. In addition, many of Kerensky’s contemporaries, who supported him, perceived him as Napoleon. Since the style of his behavior and speech reminded them of the French Revolution, they believed that he would have just as strong personality as Napoleon Bonaparte had. Finally, it should be noted that the lack of understanding by the White movement leaders in Southern Russia of the unique role Kerensky played in the political arena was one of the reasons for the country slipping down to the Civil War.